2008
DOI: 10.1001/archneur.65.9.1218
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Optical Coherence Tomography in Multiple Sclerosis

Abstract: Background: Optical coherence tomography (OCT) is a promising new method of quantifying axon thickness in the retinal nerve fiber layer (RNFL) that has been used predominantly by ophthalmologists to monitor glaucoma. Optical coherence tomography is being considered as a potential outcome measure in multiple sclerosis (MS) clinical trials, but no data exist on the reproducibility of this technique in MS centers. Objective: To determine the reproducibility of OCT measurement of mean RNFL thickness in the undilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 36 publications
0
45
0
5
Order By: Relevance
“…Previous work by Cettomai et al [16] showed good levels of inter-rater and test-retest reliability for OCT 3 (Stratus) measurements of RNFL thickness in patients with MS and disease-free controls. A more recent study, however, demonstrated that high-resolution Fourier domain OCT techniques afford an even greater degree of reproducibility of RNFL thickness and macular volume assessments [32].…”
Section: Role For Oct In Modeling Axonal and Neuronal Loss In Msmentioning
confidence: 89%
“…Previous work by Cettomai et al [16] showed good levels of inter-rater and test-retest reliability for OCT 3 (Stratus) measurements of RNFL thickness in patients with MS and disease-free controls. A more recent study, however, demonstrated that high-resolution Fourier domain OCT techniques afford an even greater degree of reproducibility of RNFL thickness and macular volume assessments [32].…”
Section: Role For Oct In Modeling Axonal and Neuronal Loss In Msmentioning
confidence: 89%
“…These OCTs offer faster scan speed and higher image resolution for RNFL imaging than conventional time-domain OCT. 2 Several studies have focused on the measurements and reproducibility of RNFL thickness using Stratus-OCT after optic neuritis (ON) and multiple sclerosis (MS). [3][4][5][6][7][8][9][10][11][12][13] In fact, lower RNFL values correlate with impaired visual function. OCT is a promising tool for evaluating atrophy in patients with ON and MS, and it could evolve into an important primary or secondary outcome measure for MS clinical trials and patient care.…”
Section: Introductionmentioning
confidence: 99%
“…This non-invasive technique thus may be useful in directing clinical response to pharmacotherapy. [1][2][3][4][5][6]16,[18][19][20][21][24][25][26][27][28] Although OCT will not replace MRI as an objective measure of MS progression, it may be a useful adjunct that provides additional information as a potential marker of neuronal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptable reproducibility has been reported by experienced centres using the Stratus OCT. 12 It has historically been used to quantify RNFL thinning in patients with multiple sclerosis (MS) and/or optic neuritis under idealized conditions. 1,3,4,[17][18][19][20][21] The Stratus OCT with Retinal Nerve Fibre Layer (RNFL) Normative Database offers clinicians a quantitative tool for the comparison of the retinal nerve fibre layer in the human retina to a database of known normal subjects. 22,23 Trial 1 required a total of 4 scans per visit: Fast Macular Thickness Map (2) and Fast RNFL Thickness (2).…”
Section: Methodsmentioning
confidence: 99%